The management correlation between metabolic index, cardiovascular health, and diabetes combined with cardiovascular disease - Zhang, Yi; Liu, Chao; Xu, Yijing; Wang, Yanlei; Dai, Fang; Hu, Honglin; Jiang, Tian; Lu, Yunxia; Zhang, Qiu (Frontiers in Endocrinology, 2023)
Background: Cardiovascular disease(CVD) remains a leading cause of morbidity and mortality in persons with types 2 diabetes mellitus(T2DM). Limited evidence suggests that multifactorial interventions for control of glucose, blood pressure, and lipids reduce macrovascular complications and mortality in patients with type 2 diabetes. However, the association between these risk factors have not been determined for such interventions. Methods: In December 10, 2018 in four cities in Anhui province, 1920 people in total. Latent category analysis(LCA) was used to explore the clustering mode of HRBs(health risk behaviors). The primary exposure were HRBs and exercise and diet interventions, the primary outcome was CVD, other variables including zMS, triglyceride-glucose index(TyG), TyG-WC, TyG-BMI, TG/HDL and cardiovascular health(CVH). Multivariable logistic regression model was used to establish the relationship of HRBs, exercise and diet interventions and CVD. Moderate analysis and mediate moderation analysis were employed by PROCESS method to explore the relationship between these variables. Results: The mean age was (57.10 ± 10.0) years old. Macrovascular complications of T2DM include coronary heart disease, cardiomyopathy, arrhythmias and cerebrovascular disease and peripheral artery disease. Elderly(χ2=22.70), no occupation(χ2=20.97), medium and high SES(χ2=19.92) , higher TyG-WC(χ2=6.60) and higher zMS(χ2=7.59) were correlated with high CVD. Many metabolic index have shown a connection with T2DM combined CVD, there was a dose-response relationship between HRBs co-occurrence, clustering of HRBs and zMS; there was a dose-response relationship between multifactorial intervention and CVH. in mediate moderation analysis, there was an association between HRB, gender, TyG, TyG-BMI and CVD. From intervene management perspective, exercise and no diet intervene was more significant with CVD, moreover, there was an association between intervene management, gender, zMS, TyG-WC, TyG-BMI, TG/HDL and CVD. Finally, there was an association between gender, CVH and CVD. Sensitivity analysis demonstrated that our results were robust. Conclusions: Globally, overall CVD affects approximately 19.9% of all persons with T2DM. CVD is a major cause of mortality among people with T2DM, accounting for approximately half of all deaths over the previous study period. Our findings suggest the potential benefits of scaling up multifactorial and multifaceted interventions to prevent CVD in patients with type 2 diabetes.